2011
DOI: 10.1614/ipsm-d-11-00017.1
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Old World Climbing Fern (Lygodium microphyllum) Spores to Herbicides

Abstract: Old World climbing fern (OWCF) is a highly invasive fern that disrupts natural communities in central and southern Florida. OCWF produces copious, wind-blown spores that have propelled its rapid invasion of Florida's natural areas over the last few decades. Current management of OWCF is limited to herbicides and natural resource managers in Florida have questioned if herbicides inhibit spore germination. This study compared spore germination rates of OWCF exposed to six herbicides and a surfactant from 1 to 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Eight treatments were applied, including three triclopyr formulations (triclopyr acid, Trycera™ herbicide, 344 g L −1 , Helena Agri-Enterprises, Collierville, TN, USA; triclopyr amine, Garlon ® 3A, 360 g L −1 , Corteva Agriscience, Indianapolis, IN, USA; triclopyr choline, Vastlan™ herbicide, 480 g L −1 , Corteva Agriscience) at two concentrations each (5.4 and 10.8 g L −1 ); glyphosate (Roundup ® Custom, 480 g L −1 , Bayer CropScience, Monheim am Rhein, Germany) at the commercial standard concentration of 14.4 g L −1 (which is equivalent to 3% v/v; Hutchinson et al 2006); and a nontreated reference. Triclopyr concentrations were chosen based upon previous research that indicated triclopyr amine applied at 7.2 g ae L −1 resulted in >90% control at 6 MAT (Hutchinson and Langeland 2007). Each treatment was replicated four times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight treatments were applied, including three triclopyr formulations (triclopyr acid, Trycera™ herbicide, 344 g L −1 , Helena Agri-Enterprises, Collierville, TN, USA; triclopyr amine, Garlon ® 3A, 360 g L −1 , Corteva Agriscience, Indianapolis, IN, USA; triclopyr choline, Vastlan™ herbicide, 480 g L −1 , Corteva Agriscience) at two concentrations each (5.4 and 10.8 g L −1 ); glyphosate (Roundup ® Custom, 480 g L −1 , Bayer CropScience, Monheim am Rhein, Germany) at the commercial standard concentration of 14.4 g L −1 (which is equivalent to 3% v/v; Hutchinson et al 2006); and a nontreated reference. Triclopyr concentrations were chosen based upon previous research that indicated triclopyr amine applied at 7.2 g ae L −1 resulted in >90% control at 6 MAT (Hutchinson and Langeland 2007). Each treatment was replicated four times.…”
Section: Methodsmentioning
confidence: 99%
“…Greenhouse and field trials examining the effectiveness of triclopyr amine resulted in 100% necrosis for 10 wk posttreatment (Hutchinson and Langeland 2007). Triclopyr amine treatments, even at high rates of 6.7 kg ae ha −1 (6 lb ae acre −1 ) resulted in excellent control of L. microphyllum with a concomitant increase in native vegetation and species richness (Hutchinson and Langeland 2007). In addition, triclopyr is absorbed more thoroughly by L. microphyllum at 60% when compared with the standard treatment of glyphosate at 31%, although most of the chemical remains in the leaves, showing minimal basipetal translocation regardless of the treatment (Hutchinson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lygodium microphyllum is difficult to manage using controlled burns, mechanical removal, or herbicide applications due to the plant's ability to regenerate from underground rhizomes (Stocker et al 1997;Goolsby et al 2003, Hutchinson et al 2006. Despite satisfactory kill of aerial vines from herbicides, 3-5% of the L. microphyllum individuals regrow and require repeated treatments to achieve mortality of the perennial underground rhizomes Lockhart 2007;Boughton & Pemberton 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid spread of L. microphyllum, its impact on native communities, and the lack of effective long-term control using conventional management techniques prompted the start of a classical biological control program in 1997 (Goolsby et al 2003;Hutchinson et al 2006). The ongoing search for potential biological control agents has focused on Asia and Australia (Pemberton 1998;Goolsby et al 2003).…”
mentioning
confidence: 99%